2018
DOI: 10.1055/a-0764-4974
|View full text |Cite
|
Sign up to set email alerts
|

Augenprothetische Rehabilitation in Deutschland heute – Versorgungsmöglichkeiten, Handhabung, Komplikationen und psychologische Aspekte

Abstract: Zusammenfassung Hintergrund Eine adäquate Versorgung mit einer optisch ansprechenden Augenprothese nach dem Verlust eines Auges ist nicht nur aus rein kosmetischen Gründen essenziell, sondern erleichtert vor allem eine gute soziale und psychische Rehabilitation. Fragestellung Es soll eine Übersicht über den aktuellen Stand der augenprothetischen Versorgung in Deutschland erstellt werden. Dabei wird auf die neuesten klinischen Erkenntnisse, die Handhabung der Augenprothesen sowie auf typisch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 67 publications
(209 reference statements)
0
6
0
Order By: Relevance
“…Enucleation, whether due to therapeutic or traumatic reasons, is a profoundly distressing procedure resulting in irreversible disability. 1 Orbital correction typically involves the use of intraocular implants and removable prostheses, which are managed by ophthalmologists and patients themselves. 4 These implants and prostheses are typically crafted from either inert materials such as silicone, glass, or methyl methacrylate or biointegrated materials like hydroxyapatite and porous polyethylene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Enucleation, whether due to therapeutic or traumatic reasons, is a profoundly distressing procedure resulting in irreversible disability. 1 Orbital correction typically involves the use of intraocular implants and removable prostheses, which are managed by ophthalmologists and patients themselves. 4 These implants and prostheses are typically crafted from either inert materials such as silicone, glass, or methyl methacrylate or biointegrated materials like hydroxyapatite and porous polyethylene.…”
Section: Discussionmentioning
confidence: 99%
“…Enucleation is a life-changing, highly distressing event. 1 Aside from loss of vision, cosmetic and aesthetic aspects are most important concerns. 1,2 Orbital corrections are performed with intraocular implants and removable prostheses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most previous studies have not shown an absolute tear volume deficiency but rather a poor distribution of tears resulting in the absence of a sufficient tear film over the anterior surface which in turn could lead to dry socket complaints [ 1 , 2 ]. Although more than 50% of all prosthetic eye wearers had at least mild dry socket symptoms, only 15% used artificial tears or ointments suggesting that dry socket symptoms might be accepted by anophthalmic patients as normal in the same way that they accept discharge to a certain degree or perhaps there is a lack of knowledge about DASS and/or of an evidence-based treatment concept [ 1 6 , 11 , 13 , 15 , 16 ]. In addition, despite more intensive care of the anophthalmic socket with eye ointments compared to the fellow eye, patients had significantly more symptoms, higher inflammation, and higher tear film osmolarity at the anophthalmic socket compared to the healthy side.…”
Section: Discussionmentioning
confidence: 99%